2016
DOI: 10.4209/aaqr.2015.08.0529
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Chemical Characteristics of Atmospheric Aerosol Particles and its Light Extinction Coefficients over Pune, India

Abstract: The present study has been conducted to characterize atmospheric aerosol particles in terms of carbonaceous species and ionic constituents for a yearlong period at Pune, India. This study provides the evidence for the ionic chemistry, secondary aerosols formation, temporal variability and its climatic effect in the atmosphere. The average concentrations of PM 2.5 and PM 10 were 109.6 ± 23.2 and 166.9 ± 4 µg m -3 , respectively, by far exceeding National Ambient Air Quality (NAAQ) and World Health Organization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 66 publications
1
1
1
Order By: Relevance
“…A ratio of 6-8 is reported over northwestern India (viz., Ahmedabad, Mount Abu) and northern India (viz., Allahabad, Hisar) whereas a ratio less than 3 (Mumbai) is detected over western India and eastern India (viz., Bhubaneswar). Annual mean of the ratio of OC to EC obtained in the present study is 1.5 to 2 times higher than the ratios reported in Chatterjee et al (2012) and Panda et al (2016) over eastern India while this ratio is 2 times lower than the ratio reported over northern, northwestern and western India (Rengarajan et al, 2007;Ram et al, 2008;Rastogi and Sarin, 2009;Tiwari et al, 2013;Safai et al, 2014, Pipal et al, 2016. Inferences referred from the above studies showing a high OC to EC ratio is attributed to the predominance of biomass burning over the specific regions (Rengarajan et al, 2007;Ram et al, 2008;Rastogi and Sarin, 2009;Rastogi et al, 2015).…”
Section: Characteristics Of Organic and Elemental Carbonaceous Aerosol Fractionscontrasting
confidence: 61%
“…A ratio of 6-8 is reported over northwestern India (viz., Ahmedabad, Mount Abu) and northern India (viz., Allahabad, Hisar) whereas a ratio less than 3 (Mumbai) is detected over western India and eastern India (viz., Bhubaneswar). Annual mean of the ratio of OC to EC obtained in the present study is 1.5 to 2 times higher than the ratios reported in Chatterjee et al (2012) and Panda et al (2016) over eastern India while this ratio is 2 times lower than the ratio reported over northern, northwestern and western India (Rengarajan et al, 2007;Ram et al, 2008;Rastogi and Sarin, 2009;Tiwari et al, 2013;Safai et al, 2014, Pipal et al, 2016. Inferences referred from the above studies showing a high OC to EC ratio is attributed to the predominance of biomass burning over the specific regions (Rengarajan et al, 2007;Ram et al, 2008;Rastogi and Sarin, 2009;Rastogi et al, 2015).…”
Section: Characteristics Of Organic and Elemental Carbonaceous Aerosol Fractionscontrasting
confidence: 61%
“…Present OC and EC concentrations of PM 2.5 were similar to those measured in Xiamen-Putian, Tianjin-China, Hong Kong and Seoul (27) (28)(29). Whereas, OC and EC concentration was lower than the Indian cities, those measured in the Indo Gangetic Plain (30), Jabalpur & Udaipur (31), Agra (32), Delhi(33) and Pune(34). WSOC is one of the major components of the total watersoluble composition of atmospheric aerosols, contributing to the number density of cloud condensation nuclei (CCN).…”
supporting
confidence: 69%
“…Pune is a major Information Technology (IT) hub along with automotive (domestic and international) manufacturing units. Several large and small scale glass, sugar, and forging industries also contribute to the growing criteria pollutant concentration at Pune [50]. The contribution of CO and NO 2 among the criteria pollutants, attributed to by sugar factories and heavy textiles industries in Solapur, led the MPI towards the mitigation category.…”
Section: Assessment Of Prioritized Air Quality Managementmentioning
confidence: 99%